Mathematical preparation of first-year students of applied informatics for studies at the university of economics - Prysak, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
Mathematics is one of the main subjects conducted in the first year of economic studies. At the Faculty of Applied Informatics at the University of Economics in Kraków, mathematics accompanies students not only in the first year, but also throughout the entire course of studies, being an essential factor of either their further success or problems in studying. Therefore, both the proper preparation in this field acquired in secondary school, as well as the awareness of the importance of this subject, are essential factors influencing the efficiency of the undertaken studies. In this article, I will present the results of the survey research conducted among the first-year students at the Faculty of Applied Informatics at the UEK on the awareness of the necessity for mathematical knowledge in the process of efficient studying. I will also discuss the results of determining their actual mathematical skills acquired in secondary school on the basis of the research conducted in the academic years 2011/2012, 2012/2013 and 2013/2014 with the use of exemplary exercises from the matura final exam at the basic and extended level. On this basis, the conclusions serving as the starting point for further research on mathematical classes in the first year of studies have been drawn. The obtained information can prove useful for academic teachers in the proper conducting of classes on mathematical subjects. The article also contains general reflections and conclusions on the mathematical education of students of economic studies.
Didactics of Mathematics, 2015, Nr 12 (16), s. 93-110
Keywords: mathematical preparation; didactics of mathematics; economic faculties